Sound of green innovation in merdeka curriculum learning science based on basic education of Ambon city - Papilaya, Pamella Mercy; Leiwakabessy, Fredy; Salhuteru, Chtherine (Program Studi Pendidikan Biologi, Pascasarjana, Universitas Pattimura, 2025)
Maluku is an island area with small islands in the islands education that needs to be covered with the purpose of: 1) protecting, considering, rehabilitating, utilizing and enriching natural resources on small islands and an ecological system on a sustainable person; 2) strengthens the participation of the community and government agencies, and encourage community initiatives in the management of natural resources and small islands to achieve justice, balance and sustainability; 3) create social, economic, and cultural values-society through the role of society in utilizing natural resources and small islands. Actually the education unit of currency is developed with diversification principle, a new innovation in the field of science education is Sound of Green (SOG) involves environmental as a source of learning. This study aims: 1) Knowing the increase in the understanding of the student's concept using the Sound of Green approach empowering the Estemic Plant Maluku in the village of attractive city of Ambon City and 2). Knowing the thinking of the Cratif's thinking of the students using the Sound of Green approach empowering the Estemic Plants Maluku in the village of the attractiveness of the city of Ambon City. The results of statistical analysis were found there was a critical thinking difference of garway gasid carbon treatment in different places in the students of JMP City Ambon. The type of local Makuku Fruit food, can now be used to be the type of food and drinks liked by many people. Learning with PJBL is very helpful in developing student creativity thinking and innovating creating products that can be utilized by the community in everyday life.